2010
DOI: 10.1007/s00436-010-1988-6
|View full text |Cite
|
Sign up to set email alerts
|

Croton cajucara crude extract and isolated terpenes: activity on Trypanosoma cruzi

Abstract: Croton cajucara is a plant found in the Amazon region and is known for its medicinal properties. The effects of the methanolic extract of the stem bark of C. cajucara (MCC) and of the isolated terpenes, trans-dehydrocrotonin (t-DCTN) and acetyl aleuritolic acid (AAA), were investigated using four isolates of Trypanosoma cruzi. In assays with trypomastigotes, the extract was more active than the isolated compounds, presenting IC(50) in the range of 10 to 50 μg/mL. The trypanocidal effect of MCC, AAA and benznid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 66 publications
1
10
0
4
Order By: Relevance
“…For example, some species of the Croton genus can be cited, whose studies have confirmed its anti-inflammatory, anti-ulcerogenic, antimutagenic, anti-estrogenic and hypoglycemic (ROSA et al, 2003), antinociceptive (OLIVEIRA et al, 2001), antifungal (SOUZA et al, 2006), antibacterial RODRIGUES et al, 2009), anti-leishmaniosis (ROSA et al, 2003), anti-Trypanosoma cruzi (CAMPOS et al, 2010), larvicide (LIMA et al, 2006) and as a central nervous system depressor (LAZARINI et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some species of the Croton genus can be cited, whose studies have confirmed its anti-inflammatory, anti-ulcerogenic, antimutagenic, anti-estrogenic and hypoglycemic (ROSA et al, 2003), antinociceptive (OLIVEIRA et al, 2001), antifungal (SOUZA et al, 2006), antibacterial RODRIGUES et al, 2009), anti-leishmaniosis (ROSA et al, 2003), anti-Trypanosoma cruzi (CAMPOS et al, 2010), larvicide (LIMA et al, 2006) and as a central nervous system depressor (LAZARINI et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Foram isolados ainda três esteróides e dois flavonóides com atividades farmacológicas, porém em concentrações minoritárias (Maciel et al, 2000). C. cajucara possui óleo volátil rico em linalol, além de já terem sido identificados para a espécie diterpenos e esteróis, o que explica a atividade anti-inflamatória, antinociceptiva, antifúngica (Souza et al, 2006), anti-leishmaniose (Rosa et al, 2003) e anti-Trypanossoma cruzzi (Campos et al, 2010).…”
Section: O Gênero Croton Lunclassified
“…Os esqueletos estruturais mais comuns são: labdanos, cauranos, seco-cauranos, cembranóides, clerodanos, neoclerodanos, halimanos, isopimaranos, traquilobanos e ésteres de forbol (Salatino et al, 2007) (Maciel et al, 1998;Grynberg, 1999;Campos et al, 2010). Outras espécies com clerodanos bioativos são C. lechleri -clerodanos com atividade antioxidante (De Marino, 2008), C. palanostigma -atividade antitumoral (Campos et al, 2010) e C. cajucara da qual foi isolada a trans-desidrocrotonina (DCTN) com atividade antitumoral (Grynberg, 1999).…”
Section: óLeos Voláteisunclassified
See 2 more Smart Citations